E MAMOM SE FEZ CARNE: A idolatria do dinheiro nos escritos de Ellen G. White - Vital, Elivelto Roberto (2021)
Life was so submitted to money that, a world where money does not exist, seems inconceivable. Created to be a facilitating means, money became an end, and, finally, it was absolutized, deified. This deification of money is discussed by current authors, who were able to analyze this issue from its root, in the mythical systems that drive the idolatry of money, reaching its fruits, in the death of the poor, social inequality, loss of dignity and more. The idolatry of money occurs in the presence of his twin sister, the idolatry of the market. The 19th century served as a large greenhouse, in which, the idolatry of money gained strength after the metabolism provided by American industrial capitalism. During this period not only did business and capital flourish, but also those who felt compelled to warn about the temporal and eternal dangers of the idolatry of money. In this context, Ellen Gould White emerges as a prophetic voice, announcing that Mammon worshipers should abandon their idolatrous practice. Her writings, fruit of his ministry, often addresses the theme of the idolatry of money. In her pastoral practice, the love of money, “the root of all evils”, is denounced, and the lover of money is called to conversion.